Validating the dual evolutionary foundations of political values in a US sample - Lavender Forsyth, Guy A.; Chaudhuri, Ananish; Atkinson, Quentin Douglas (Frontiers in Psychology, 2023)
Psychological research repeatedly identifies two dimensions of political values. Recent work argues that these dimensions reflect the dual evolutionary foundations of human social and political life: a trade-off between cooperation and competition that generates differences in values about social inequality, and a trade-off in managing group coordination that generates differences in values about social control. Existing scales used to measure political values, however, were created prior to this framework. Here, we introduce the Dual Foundations Scale, designed to capture values about the two trade-offs. We validate the scale across two studies, showing it accurately and reliably measures both dimensions. Our results support key predictions of the dual foundations framework and pave the way for future work on the foundations of political ideology.